Chapter Terminologia e lessicografia: riflessioni sulla denominazione delle pratiche terminologiche nel XXI secolo - Grimaldi, Claudio (Proceedings e report, 2021)
This contribution aims to propose a reflection that is inserted in a perspective of the history of lexicography, on the one hand, and of semantics, on the other. The first objective of this work is to retrace how the denominations generally attributed to lexicographic and terminographic practice have been structured and lexicalized over the centuries. In the second part of this work, the paper mainly reflects on the use of the names of lexicographic resources ("dictionary", "glossary", "vocabulary") in terms of terminology. This investigation objective arises from the hypothesis of a improper use of these names in different fields of application, especially when non-linguists use these names for products that claim to be of a terminological nature.